Moderating effects of performance measurement use on the relationship between organizational performance, measurement diversity and product innovation - Yaghi , Bassil A. (Cranfield University, 2007)
This study sets'out to address the question of whether the effect of organizational' performance measurement diversity on product innovation will differ depending on how organizational performance measures are used. There is strong empirical evidence that many companies who are successful today are less likely to be successful in the future because they fail to innovate. It is surprisingly then, that when everyone stresses the importance of innovation, there are many organizations adopting performance measurement systems, which may constrain their innovativeness. Currently, there are three differing perspectives on the effect of measurement on a firm's propensity to innovate. Moreover, each of these has empirical evidence to support its argument. The first perspective views measurement as constraining innovation because it impedes creativity, experimentation, and search in firms. The second perspective views measurement as helping innovation because it triggers search, facilitates decision-making, and increases risk-taking. The third perspective views measurement as having insignificant or little impact on innovation because it is used primarily for signalling. A possible explanation of the contradiction in the empirical findings of these studies is that they generally ignore how measurement is used. Therefore, using the behavioural theory of innovation, I argue that one possible way of resolving the contradictory findings is by incorporating measurement use as a moderating variable. Using data from a cross-sectional, large-scale, probability sample survey of 145 UK manufacturing firms, I show that organizational performance measurement diversity interacts with performance measurement use to determine product innovation. My findings suggest that the extent to which a firm offers new products will be more positively (negatively) associated with performancemeasurement diversity when diagnostic use is high (low) holding interactive use constant and will be more negatively (positively) associated with performance measurement diversity when interactive use is high (low) holding, diagnostic use constant.